Ultrasound-Guided Hydrodissection Provides Complete Symptom Resolution in Radial Tunnel Syndrome: A Case Series and Scoping Review on Hydrodissection for Radial Nerve Pathology. Issue 9 (September 2022) - Gill, Benjamin; Rahman, Rafid; Khadavi, Michael
Abstract: This study analyzes the effectiveness of ultrasound-guided hydrodissection (HD) perineural as a treatment for radial tunnel syndrome (RTS). A literature search was performed along with retrospective analysis of local cases to assess outcomes and safety of this procedure. In the case series, surgical candidates, defined as cases with over 80% but temporary relief after diagnostic injection, were treated with ultrasound-guided HD. Of 22 patients who received ultrasound-guided diagnostic injections, 11 proceeded to HD. All HD patients experienced complete and lasting symptom resolution for a minimum of 2 years, and none required surgery. Thorough literature review provided seven studies, which fulfilled inclusion criteria. Sixty-one patients are represented in the literature. All studies reported significant benefit to pain symptoms with HD of radial nerve, with five specifying over 90% improvement. No adverse effects from HD were noted in any study. Ultrasound-guided HD of the radial tunnel has potential to be a surgery sparing treatment for RTS.